An improved torque sensorless speed control method for electric assisted bicycle with consideration of coordinate conversion - Li, Tinghua; Yang, Qinghua; Tu, Xiaowei; Ren, Bin (IEEE/CAA journal of automatica sinica, 2020)
In this paper, we propose an improved torque sensorless speed control method for electric assisted bicycle, this method considers the coordinate conversion. A low-pass filter is designed in disturbance observer to estimate and compensate the variable disturbance during cycling. A DC motor provides assisted power driving, the assistance method is based on the real-time wheel angular velocity and coordinate system transformation. The effect of observer is proved, and the proposed method guarantees stability under disturbances. It is also compared to the existing methods and their performances are illustrated through simulations. The proposed method improves the performance both in rapidity and stability.